The Unknown Country: Death in Australia, Britain and the USA
XV, 268 p.
Keywords: In a strategy deliberately counter to many earlier texts which focus on social aspects of death and dying this book will not examine death through the social prism of US or British culture alone. Drawing only on material from a single society gives readers the misleading impression of a universal experience. As a text in the sociology of death and dying this volume examines culture-specific images and experiences of death in three major western societies - Australia, Britain and the USA.